Effect of resealing on microleakage of resin composite restorations in relationship to margin design and composite type - Antonson, Sibel A; Yazici, A. Ruya; Okte, Zeynep; Villalta, Patricia; Antonson, Donald E; Hardigan, Patrick C (European Journal of Dentistry, 2012)
Objective: To determine the relationship between margin preparation design and resin-composite type on microleakage with or without re-application of surface-penetrating sealant.Methods: Class-I resin-composite restorations were completed for 128 extracted human molars. Half of the margins were beveled, the other half, butt-joint. Half of each group was restored with Filtek-Supreme (FS), the other half with Esthet-X (EX) using their respective adhesive systems. Margins were etched and sealed with a surface-penetrating sealant, Fortify. The samples were stored in water 24h, and thermocycled (5,000 cycles, 5°C-55°C). Then, samples were abraded using a toothbrush machine (6,000 strokes). Half of the restorations from each sealant group (n=16) were resealed, and the other half had no further treatment. Thermocycling and tooth brushing were repeated. The samples were sealed with nail polish, immersed in methylene-blue for 8h, sectioned, and magnified digital photographs were taken. Three examiners assessed dye penetration. A 2x2x2 multi-layered Chi-Square analysis, using Cochran-Mantel-Haenszel test was conducted for statistical analysis.Results: No difference was observed between sealed and resealed FS and EX restorations with butt-joint margins. In beveled margins, resealing caused significantly less microleakage (P<.01). No differences were found between restorations either sealed or resealed with bevel margins. In butt-joint margins, at the leakage level deeper than 2/3 of the preparation depth, resealed FS showed less microleakage than EX resealed restorations (P<.01).Conclusion: Resealing reduced microleakage in bevel margins, however, in butt-joint margins resealing did not affect the leakage. A significant statistical relationship exists between and within resealing, margin preparation design, type of composite, and microleakage. (Eur J Dent 2012;6:389-395)
Keywords: Resin-composite margin design; bevel; butt-joint; surface penetrating sealant; microleakage